New Luminescence and Radiocarbon Dates for Kanem-Borno Fired-Brick Elite Sites in Kanem, Chad: Bayesian Chronological Modelling of Settlement Construction. - Magnavita, Carlos; Lindauer, Susanne; Adjbane, Adoum Casimir (African Archaeological Review, 2025)
Five fired-brick sites, tentatively attributed to the Kanem-Borno State, were test-excavated, and samples of fired bricks and wood charcoal were dated using optically stimulated luminescence (OSL) and accelerator mass spectrometry (AMS). Although OSL yielded larger standard deviations compared to radiocarbon dating, both methods produced chronologically significant results. In addition to confirming that the sites were constructed during Kanem-Borno's rule over Kanem, the new dates support earlier suggestions of multi-phase construction of similar nearby locations. To systematically analyze the growing body of chronometric data from Kanem, we employed Bayesian chronological modelling. This method not only identifies potential stratigraphic and chronological outliers but also provides probabilistic evidence for the multi-phase development of these sites.